2008
DOI: 10.1111/j.1523-1739.2008.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of the Area and Shape of Patches to the Diversity of Multiple Taxa

Abstract: Although enhancing reserve shape has been suggested as an alternative to enlarging nature reserves, the importance of reserve shape relative to reserve area remains unclear. Here we examined the relative importance of area and shape of forest patches to species richness, species composition, and species abundance (abundance of each species) for 3 taxa (33 birds, 41 butterflies, and 91 forest-floor plants) in a fragmented landscape in central Hokkaido, northern Japan. We grouped the species according to their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 47 publications
1
49
1
2
Order By: Relevance
“…Bohning-Gaese 1997;Farina 1997;Grand and Cushman 2003;Kati and Sekercioglu 2006;Kati et al 2009). Shape irregularity is found to be positively associated with bird abundance across different habitats and spatial scales, but also negatively associated with the winter bird species abundance in deciduous forests, as well as with the species richness of boreal forest species (Brennan and Schnell 2005;Yamaura et al 2008;Caprio et al 2009). We also found that the vertical structural complexity, and patch shape irregularity affected the species richness of woody plants.…”
Section: Drivers Of Species Richnessmentioning
confidence: 94%
“…Bohning-Gaese 1997;Farina 1997;Grand and Cushman 2003;Kati and Sekercioglu 2006;Kati et al 2009). Shape irregularity is found to be positively associated with bird abundance across different habitats and spatial scales, but also negatively associated with the winter bird species abundance in deciduous forests, as well as with the species richness of boreal forest species (Brennan and Schnell 2005;Yamaura et al 2008;Caprio et al 2009). We also found that the vertical structural complexity, and patch shape irregularity affected the species richness of woody plants.…”
Section: Drivers Of Species Richnessmentioning
confidence: 94%
“…over plant species richness, although results are not always conclusive. Along the same line, numerous authors have also shown the importance of taking into account the effect of patch shape over species richness (Dzwonko and Loster 1992;Bastin and Thomas 1999;Hill and Curran 2003;Petit et al 2004;Heegaard et al 2007;Cousins and Aggemyr 2008;Yamaura et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…There have been numerous general analyses of edge effects on patterns of species richness and diversity (e.g. Yahner 1988;Kiviniemi and Eriksson 2002;Yamaura et al 2008;van Halder et al 2011), but studies documenting avoidance or preference of habitat edges by particular species of conservation interest, the results of which could be used in conservation practice, have been less popular (see reviews in Fahrig 2003;Ries et al 2004). Furthermore, species-specific studies of edge use have been predominantly conducted in vertebrates, especially mammals and birds, and considerably less abundant in other taxa (Ries et al 2004;Fletcher et al 2007).…”
Section: Introductionmentioning
confidence: 99%